Naira Hambardzumyan, Elpis Kesaratsyan. Essays, Poems, Letters - Makaryan, Albert (Bulletin of Yerevan University B: Philology, 2025)
In 2025, the "Edit Print" publishing house published the collection "Elpis Kesaratsyan. Essays, Poems, Letters", compiled and edited by writer, literary critic, candidate of philological sciences, associate professor Naira Hambardzumyan, which was published under the patronage of literary critic, bibliographer Yovsep Nalbandian, within the framework of the "Research in the Fields of Social Sciences, Armenology and Humanities-2024" competition (24SSAH-6B006) of the RA State Committee for the Promotion of Armenian Literature. The book is an important contribution to the restoration, illumination and popularization of the literary heritage of Armenian intellectual women.
Keywords: Elpis; Kesaratsyan; Essays